Effects of matrix metalloproteinase inhibitor doxycycline and CD147 antagonist peptide-9 on gallbladder carcinoma cell lines - Shihang Wang; Chao Liu; Xinjiang Liu; Yanxin He; Dongfang Shen; Qiankun Luo; Yuxi Dong; Haifeng Dong; Zhigang Pang (Tumor Biology)
Gallbladder carcinoma is the most common and aggressive malignancy of the biliary tree and highly expresses CD147, which is closely related to disease prognosis in a variety of human cancers. Doxycycline exhibited anti-tumor properties in many cancer cells. CD147 antagonist peptide-9 is a polypeptide and can specifically bind to CD147. The effect of these two drugs on gallbladder cancer cells has not been studied. The aim of this study is to investigate the effect of doxycycline and antagonist peptide-9 on gallbladder carcinoma cells and the possible mechanism of inhibition on cancer cell of doxycycline. To investigate the effects of doxycycline and antagonist peptide-9 on gallbladder carcinoma cells (GBC-SD and SGC-996), cell proliferation, CD147 expression, and early-stage apoptosis rate were measured after treated with doxycycline. Matrix metalloproteinase-2 and matrix metalloproteinase-9 activities were measured after treated with different concentrations of doxycycline, antagonist peptide-9, and their combination. The results demonstrated that doxycycline inhibited cell proliferation, reduced CD147 expression level, and induced an early-stage apoptosis response in GBC-SD and SGC-996 cells. The matrix metalloproteinase-2 and matrix metalloproteinase-9 activities were inhibited by antagonist peptide-9 and doxycycline, and the inhibitory effects were enhanced by combined drugs in gallbladder carcinoma cell lines. Taken together, doxycycline showed inhibitory effects on gallbladder carcinoma cell lines and reduced the expression of CD147, and this may be the mechanism by which doxycycline inhibits cancer cells. This study provides new information and tries to implement the design of adjuvant therapy method for gallbladder carcinoma.